KESANTUNAN TINDAK TUTUR IMPERATIF DALAM PENGAJARAN BAHASA INGGRIS PADA MAHASISWA DI KABUPATEN DHARMASRAYA - Lusiana Lusiana; Nidya Fitri (Universitas Andalas, 2016)
Imperatives politeness strategy are nessecary in the process of teaching and learning, particularly in the English language teaching. In the process of teaching and learning expected lecturer is able to establish communication with the good atmosphere to create in order for the communicative and knowledge transferring can also be well received. But the fact that of the real presence yet shows the synchronization relationships between lecturer and students in the classroom. This is impacting on the quality of the process and learning outcomes of the students. Therefore, the politeness imperatives strategy is done to get data and information can be used as consideration and appropriate strategies that improve the quality of teaching and learning. So that teaching can be obtained for purposes of the maximum, especially in the teaching of the language of the collage student at Dharmasraya.Data collection is done using non participant observation method the method. In this research, the method refers to the use of the imperative acts both in language teaching. Then, the technique used is the participant technique and basic technique is sadap technique. Data analysis is used pragmatic method of indeterminate become a partner between collage students and lecturer. The results showed that the strategy of politeness applied in language teaching, especially in the college students semester 2 PGSD FKIP Department courses at the Indonesia Dharmas University is politeness strategy the context in which the context of the follow up politeness is imperative in the form of said force, invite, sent, urging, pleading, suggest, and ruled with the discovery of three of the four functions of the language according to the Leech (1993:164) competitive, konvivial, and collaborative. However, the function of language that is often used is a function collaborative language. The success rate of the use of imperative strategy is very effective in English language teaching so that learning can be implemented properly. Keywords: error analysis, modification, Doushi Renyoukei, morphological, syntactic